Foreign co-operation of Polish regions: The principal areas - Malgorzata Pacuk (European Regional Science Association (ERSA), 1998)
Between December 1996 and March 1997 a survey was carried out on the basis of a questionnaire prepared by the author. The answers, which were gathered from all Poland's voivodships, provided comprehensive knowledge on the various forms of international co-operation entered into by voivodships (without accounting for local scale) in 1990-1996. Analysis and comparison of the survey results show that at present there is a relatively powerful lobby in Polish administrative organs pushing for educational and cultural co-operation, while support for economic co-operation appears rather poor, which is mainly concerned with the small private sector. The questionnaires hardly ever mentioned small and medium-sized enterprises, which are so important for transforming and diversifying the economic tissue of Polish voivodships. We might even argue, that the foreign co-operation involving voivods in the branch dimension derives from the departmental structure of voivodship offices. The interest of office structures in this area appears very strong and is helping to minimise what is one of the major problems of structural policy. This must make it difficult for Polish regions to perform their principal strategic function: reconverting the regional production base and at the same time restructuring large industrial sectors.
Keywords: 330